Considerations regarding monistic method in geographical research with environmental emphasis - Diniz, Marco Túlio Mendonça (UFPR, 2009)
Environmental issues exist since last century as the biggest problems to be faced by humankind, and particularly, by science. Classical science was said to have the solution for all natural and social matters in the world. Geography also had the influence of rationalism that led, within itself, to the attempt of obtaining methods that were superior to other ones. Geography has the environment as its study object since its foundation, although the latter has been put aside. However, it returns as an issue to be analyzed by geographers in the current century. We wonder if there is a method able to deal with all issues on environmental order in Geography.